QUANTIFICATION OF CLINICAL-BIOLOGICAL INDICES NECESSARY FOR THE EVALUATION OF IMPLANTABLE PATIENTS - Monica Apostol; Siminiuc Petruta - Iuliana; Cerasela Ciocoiu; Emilian Crețu; Iana Rusu; Mirela Șmadici; Norina Forna (Romanian Dental Association for Education, 2022)
Aim of the study The predictability of osseointegrated root form implants with well-documented and long-term functional and esthetic outcomes has led to their acceptance as a practical treatment modality in modern dentistry for rehabilitation purposes in fully edentulous and partially dentate patients, or for single-tooth replacement. The success of implant treatment and maintenance of its highly desirable outcomes are dependent upon several prerequisites to accomplish a dynamic association of functional and esthetic results. These factors may include adequacy of bone quantity and quality, biocompatibility of implant biomaterial and characteristics of implant surface, absence of surgical complications, absence of peri-implantitis, and prevention of excessive loading. Moreover, direct and indirect systemic factors that influence the host response appear to be of great relevance to the prediction of risk groups for implant loss. Despite a few contraindications and a documented long-term success rate, it is widely recognized that dental implants sometimes can be susceptible to healing complications or disease conditions that eventually may result in implant loss. Thus, the focus of implant research has shifted from demonstrations of clinical success to more specific attempts at identification of factors that may contribute to implant failure. Material and methods include Prosthetic Factors and Periodontal Factors. In this section we discuss about many type of restoration and type of cement for cementation. Also, includes clinical parameters devided in bleeding on probing, clinical attachements loss, Probing Depth, Suppuration, radiographic evaluation and gingival recession. Results At baseline, patients fell into the following risk profiles: low-risk (n = 102, 28.9%), moderate-risk (n = 68, 19.3%), high-risk (n = 77, 21.8%), and very high-risk (n = 106, 30%). The incidence of peri-implant disease over five years was 24.1% (n = 85 patients). The RR for the risk groups was 5.52 (c-statistic = 0.858). The RR for a longer recall regimen was 1.06, corresponding to a PAR of 5.87%. Conclusions Maintaining soft tissue health is as important in the long-term maintenance and success of implants as osseointegration.